2012
DOI: 10.1103/physreve.86.036216
|View full text |Cite
|
Sign up to set email alerts
|

Generalized synchronization in mutually coupled oscillators and complex networks

Abstract: We introduce a novel concept of generalized synchronization, able to encompass the setting of collective synchronized behavior for mutually coupled systems and networking systems featuring complex topologies in their connections. The onset of the synchronous regime is confirmed by the dependence of the system's Lyapunov exponents on the coupling parameter. The presence of a generalized synchronization regime is verified by means of the nearest neighbor method.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 31 publications
0
42
0
15
Order By: Relevance
“…Thus, in general, the notion of GS in mutually coupled systems needs much indepth investigation and in particular in distinctly different systems with different fractal dimensions involving time-delay. Indeed, recent investigations have revealed that GS is essentially more likely to occur in complex networks (even with identical nodes) [15] due to the large heterogeneity (degree distribution) of many natural networks [21].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in general, the notion of GS in mutually coupled systems needs much indepth investigation and in particular in distinctly different systems with different fractal dimensions involving time-delay. Indeed, recent investigations have revealed that GS is essentially more likely to occur in complex networks (even with identical nodes) [15] due to the large heterogeneity (degree distribution) of many natural networks [21].…”
mentioning
confidence: 99%
“…Thus, in general, the notion of GS in mutually coupled systems needs much indepth investigation and in particular in distinctly different systems with different fractal dimensions involving time-delay. Indeed, recent investigations have revealed that GS is essentially more likely to occur in complex networks (even with identical nodes) [15] due to the large heterogeneity (degree distribution) of many natural networks [21].It is important to recall that the above mentioned studies [3][4][5][6][7][8][9] have demonstrated only phase synchronization (PS) among such distinctly different complex systems, while the natural choice of GS in them has been largely neglected, except for the important study of Zheng etal [14] on low-dimensional systems without delay and without a substantial difference in their fractal dimension. Further, depending on the relation between PS and GS [26] in such systems, which remains unclear, our understanding on their evolutionary mechanism, dynamical and functional behavior may need to be reinvestigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For the unidirectionally coupled systems the evolution of drive system does not depend on the evolution of response system, but for bidirectionally or mutually coupled systems the state variables of each system will depend on the state variables of the other system. So, for such a case the functional relation y = φ(x) is to be modified to the form [15,16],…”
Section: Generalized Synchronization For Mutually Coupled Systemsmentioning
confidence: 99%